2023
DOI: 10.1038/s41419-023-05790-4
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA UCA1 promotes keratinocyte-driven inflammation via suppressing METTL14 and activating the HIF-1α/NF-κB axis in psoriasis

Abstract: Keratinocytes are closely associated with innate immunity and inflammatory responses, and are dysregulated during the development of psoriasis, but the underlying mechanisms are not yet fully understood. This work aims to reveal the effects of long non-coding RNA (lncRNA) UCA1 in psoriatic keratinocytes. UCA1 was identified as a psoriasis-related lncRNA that highly expressed in psoriatic lesions. The transcriptome and proteome data of keratinocyte cell line HaCaT showed that UCA1 could positively regulate infl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 50 publications
0
6
1
Order By: Relevance
“…25 Additionally, the upregulation of UCA1 (log 2 FC: 1.97), a keratinocyte-specific lncRNA, underscores its role in the interplay between psoriatic keratinocytes and immunity. 26 While PRINS has been previously implicated in psoriasis, 10 our study did not replicate this. Given their finely tuned regulatory capacities, lncRNAs exhibit great potential as biomarkers for diagnosis, disease development and treatment in psoriasis.…”
Section: Discussioncontrasting
confidence: 72%
“…25 Additionally, the upregulation of UCA1 (log 2 FC: 1.97), a keratinocyte-specific lncRNA, underscores its role in the interplay between psoriatic keratinocytes and immunity. 26 While PRINS has been previously implicated in psoriasis, 10 our study did not replicate this. Given their finely tuned regulatory capacities, lncRNAs exhibit great potential as biomarkers for diagnosis, disease development and treatment in psoriasis.…”
Section: Discussioncontrasting
confidence: 72%
“…In hepatocellular carcinoma and colorectal cancer, METTL3 mediates the m6A modification of HIF-1α mRNA, and then extends its half-life and improves stability and translation, subsequently interacting with target genes related to glycolysis[ 34 , 35 ]. However, in cells with METTL14 knockdown used for a psoriasis study, the m6A level of HIF-1α mRNA decreased, but the protein expression increased[ 36 ]. m6A modification directly affected the translation efficiency of HIF-1α instead of the mRNA level[ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…35 Li et al also showed that the inhibition of PVT1 exon 2 could induce the growth suppression of cutaneous squamous cell carcinoma, which was caused by cellular senescence, increased p21/CDKN1A expression and cell cycle arrest. 36 However, besides skin tumors, lncRNAs also influence the pathogenesis of many skin inflammatory diseases, 33 such as psoriasis, [38][39][40][41] hidradenitis suppurativa, 42,43 atopic dermatitis. [44][45][46] Among these skin diseases, the psoriasis was the most studied one.…”
Section: Discussionmentioning
confidence: 99%